Midline Prostatic Cyst Marsupialization Using Holmium Laser. (26th May 2015) - Kilinc, Mehmet; Goger, Yunus Emre; Piskin, Mesut; Balasar, Mehmet; Kandemir, Abdulkadir
Abstract : Many of the prostatic cysts are asymptomatic and only 5% are symptomatic (Hamper et al., 1990; Higashi et al., 1990). These symptoms include pelvic pain, hematospermia, infertility, voiding dysfunction, prostatitis-like syndrome, and painful ejaculation. Treatment of prostatic cysts includes TRUSG guided drainage, endoscopic transurethral resection, and in some cases even open surgery. In the literature, endoscopic interventions use marsupialization of the midline prostatic cyst with transurethral resection (TUR) or transurethral incision with endoscopic urethrotomy (Dik et al., 1996; Terris, 1995). Holmium: YAG laser was employed for the marsupialization of the cyst wall in midline prostatic cyst treatment for the first time in the present study. Symptoms, treatment, and follow-up are presented in this paper.